Evaluation of Heavy Metal Contamination Resulting from Artisanal and Small-Scale Gold Mining Activities in Lantung District, Sumbawa - Ari Nuryaddin Putra; Joni Safaat Adiansyah; Sukuryadi Sukuryadi (Journal of Bioresources and Environmental Sciences, 2025)
Artisanal and Small-Scale Gold Mining (ASGM) activities in Ai Mual Village, Lantung Sub-district, Sumbawa Regency, have the potential to degrade environmental quality, as indicated by analysis results showing that cyanide concentrations and pH levels in water near the mining area exceed the water quality standards for Class I and II, as stipulated in Government Regulation No. 22 of 2021. The methodology employed includes spectral analysis based on vegetation indices (NDVI, ENDVI, GNDVI) and iron oxide indices, which serve as preliminary identification or anomaly visualization. These results are subsequently analyzed in more detail and validated using laboratory data on physical, chemical, and biological parameters. The results indicate that low NDVI values (≤ 0.1) and high Fe-oxide index values are distributed across active ASGM zones, suggesting substantial environmental stress on vegetation. Laboratory analysis revealed that several locations contained cyanide concentrations ranging from 0.02 to 0.06 mg/L, exceeding the quality standards set by Indonesian Government Regulation No. 22 of 2021. The low pH value (2.17) recorded at site SWL-2 indicates symptoms of acid mine drainage (AMD), which further enhances the mobility of heavy metals into aquatic systems. Biologically, SWL-1 recorded fecal coliform counts of 16,000 MPN/100 mL and total coliform at 160,000 MPN/100 mL up to 32 times the allowable limits. Conversely, SWL-2 showed low coliform levels, possibly due to acidic conditions that inhibit bacterial survival. The findings were visualized through thematic maps and spatial overlays, highlighting high-risk zones covering approximately ±65.33 hectares located in Ai Mual Village, Lantung Subdistrict .